PELAYANAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN BONGOHULAWA KECAMATAN LIMBOTO KABUPATEN GORONTALO - Agustina Biga; Apris Ara Tilome; Rusly Abdurrahman Idji (LPPM Universitas Muhammadiyah Gorontalo, 2024)
This study aims to find out how the Land and Building Tax Service in Bongohulawa Village, Limboto District, Gorontalo Regency. The research method used is a qualitative approach with a descriptive type of research. The results of the research obtained that the Land and Building Tax (PBB) service has not run well. Where based on the service indicators, it was found that the dimensions of the services studied were found: a) tangible, according to the results of the study that the tangible indicators in service were not good enough, where in the UN service the Village Government did not make the flow of services, b) reliability, in accordance with the results of the study it was found that the reliability indicators have not run well, where UN payment blanks often experience incorrect writing of names and amounts of tax bills, c) responsiveness, based on the results of the study, this indicator has not been running well enough, where in the provision of services not all employees respond well and quickly, as well as delays in the delivery of SPPT to taxpayers d) assurance, in accordance with the results of the research conducted showing that this indicator is in accordance with the expected and e) empathy, in accordance with the results of the study that this indicator has run well